Corporate sustainability and responsibility in the Cape Winelands - Deffee, Abigail (Department of Sociology, 2020)
Several studies have examined the business case of corporate sustainability and responsibility (CSR) but there is less evidence which demonstrates the lasting positive impact of CSR on society. This exploratory study examines the perceptions of business responsibility in the wine industry from the social perspective. Bound by the legacies of slavery, the Cape wine industry has been shaped by unequal social, racial and cultural dynamics of power since the 1600s. The qualitative research approach adopted was designed so as to draw out insights from key decision-makers via nine semi-structured interviews. Positioned within a holistic framework, and drawing upon systems thinking, this research produced a number of key findings. Firstly, there is some evidence of systemic CSR in the dataset; firms placed explicit emphasis on the training and upskilling of previously marginalised groups, and took collective responsibility for solving social problems. There were examples of business creativity in establishing share schemes, although the success of these in remedying deep structural inequalities remains unclear. Secondly, the findings provide evidence of paternalistic behaviours on wine estates operating within existing hegemonic power structures. The participants’ experiences of social initiatives largely equates to the empowerment of community groups via specific benevolent projects. The main conclusion drawn is that CSR in the Winelands commonly manifests as a mutation of entrenched paternalism, and thus is not a substitute for broader structural reform.